Evaluation of dysphagia severity in patients with nasopharyngeal carcinoma undergoing radiotherapy - Mahmood Bahramizadeh; Rezvaneh NAMAZI Yousefi; Francesco Ciodaro (Advances in Medicine, Psychology, and Public Health, 2025)
Introduction: Dysphagia in patients treated with radiotherapy for Nasopharyngeal Carcinoma has limited empirical evidence. The aim of this study was to identify specific foods and feeding methods recommended for these patients and to evaluate the anatomical and functional structures most affected by radiotherapy doses. Methods: Nine patients with Nasopharyngeal Carcinoma, previously treated with Radio- or Radio chemotherapy and not undergoing head and neck surgery, participated in the study. The patients had undergone either 3D Conformal Radiotherapy (3D-CRT) or Intensity-Modulated Radiotherapy (IMRT) and were evaluated using a questionnaire developed by Travalca Cupillo et al., (2011) an assessment form for adult dysphagic patients, followed by a Fiberoptic Endoscopic Evaluation of Swallowing (FEES). Results: The study revealed motor deficits primarily in the initial phases of swallowing (oral phase and pharyngeal trigger), with borderline conditions that would have been missed by a screening questionnaire, as patients did not report specific symptoms. Symptoms were even less evident in patients who underwent IMRT instead of 3D-CRT, in patients who lost less weight during radiotherapy, in patients with N0 at diagnosis, and in younger patients. Discussion and Conclusions: Patients treated with radiotherapy in the head and neck region present with various forms of dysphagia, sometimes silent. The use of proper oral hygiene and appropriate food consistencies can reduce the risk of pulmonary complications.